APLIKASI PENYELESAIAN PERHITUNGAN IPA FISIKA SMA KELAS X BERBASIS ANDROID (Information Technology and Telematics, 2014)
AbstractAndroid is an operating system based on Linux kernel modified for mobile phones such as smartphones and tablets were the work of google . Android is open source nature allows for developers to be able to modify and customize the Android OS on their devices will be created . The developers can also create a wide range of applications that can help users like apps daily prayer , prayer time reminders to applications that can be usedto help the learning process . Physics is one of the lessons are not easily perceived by most students because of the formula and units to be memorized , so the need for new methods that are used so that the learning process more enjoyable . The results obtained after the application of the calculation of class X Science Physics android based SMA is applied is easier for the students to work on assignments and lesson is no longer an excuse lazy student learning.Keywords : Android , Physics , calculations